2022
DOI: 10.3390/ijms231911821
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for the Use of Fucoidans in Clinical Oncology

Abstract: Fucoidans are natural sulfated polysaccharides that have a wide range of biological functions and are regarded as promising antitumor agents. The activity of various fucoidans and their derivatives has been demonstrated in vitro on tumor cells of different histogenesis and in experiments on mice with grafted tumors. However, these experimental models showed low levels of antitumor activity and clinical trials did not prove that this class of compounds could serve as antitumor drugs. Nevertheless, the anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 148 publications
0
11
0
Order By: Relevance
“…Fucoidans have been shown to exhibit a variety of beneficial pharmacological effects, including antitumor [ 5 , 54 , 55 , 56 , 57 , 58 ], anti-inflammatory [ 3 , 4 , 5 ], immunomodulatory [ 4 , 5 ] antioxidant [ 6 , 7 , 8 ], anticoagulant [ 5 , 59 , 60 , 61 , 62 ], antithrombotic [ 5 , 63 , 64 ], antiangiogenic [ 5 , 56 , 65 , 66 , 67 , 68 , 69 ], and antiviral [ 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Overview Of Fucoidansmentioning
confidence: 99%
See 2 more Smart Citations
“…Fucoidans have been shown to exhibit a variety of beneficial pharmacological effects, including antitumor [ 5 , 54 , 55 , 56 , 57 , 58 ], anti-inflammatory [ 3 , 4 , 5 ], immunomodulatory [ 4 , 5 ] antioxidant [ 6 , 7 , 8 ], anticoagulant [ 5 , 59 , 60 , 61 , 62 ], antithrombotic [ 5 , 63 , 64 ], antiangiogenic [ 5 , 56 , 65 , 66 , 67 , 68 , 69 ], and antiviral [ 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Overview Of Fucoidansmentioning
confidence: 99%
“…Fucoidan ( Fucus vesiculosus ) has been developed as a therapeutic nanomedicine to enhance the efficacy of immune check inhibitors (anti-PD-L1) in immunosuppressive TME [ 126 , 161 ]. It has been shown that the fucoidan-based nanomedicine IO@FuDe reduces adverse effects and extends patient survival in cancer treatments [ 5 , 126 ]. Although the development of fucoidan-based therapeutic nanoparticles is still in an early stage [ 152 ], it is important and promising to develop fucoidan as a nanotechnology-based cancer immunotherapy drug [ 162 , 163 ].…”
Section: Relevance To Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that dietary compounds or nutraceuticals such as diferuloylmethane (curcumin), plant hytoalexin (resveratrol), pentacyclic triterpenoid isolated from the root of Tripterygium wilfordii (celastrol) radiosensitized different types of cancer cells through the modulation of cell cycle, induction of apoptosis, and the regulation of TNF-α/NFκΒ and MAPK kinases activation [ 37 ]. Since the sulfated polysaccharides of brown algae, fucoidans, their derivatives, and glycosides from the starfishes, exhibited potent cytotoxic, anti-proliferative, anti-migratory, and anti-metastatic activities against human cancer cells [ 12 , 19 , 38 , 39 ] we check the idea that fucoidan from the brown alga S. cichorioides in combination with triterpene glycoside, pacificusoside D, from the starfish S. pacificus would be able to increase the inhibiting effect of low non-toxic doses X-ray radiation resulting in effective suppression of the viability and invasion of 3D melanoma cells SK-MEKL-2.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ECX contains more ingredients than fucoidan and glucosamine, e.g., hyaluronan, antioxidants and enzymes, which may in vivo improve endothelial health by exhibiting beneficial synergistic effects (e.g., protection of existing eGC against damage, synthesis of new eGC components, enhanced eGC repair). It is noteworthy that fucoidan is unlikely to be used as an individual agent alone in clinical practice but instead as a mixed dietary supplement [ 56 , 57 ]. Hence, further experiments are planned to elucidate the role of other ECX components in eGC protection.…”
Section: Discussionmentioning
confidence: 99%